Comparación de los perfiles de disolución de diazepam en tabletas genéricas 10 mg y el producto innovador - Alva Bocanegra, Ronald Javier (2009)
The goal of this study was to compare de dissolution profile of Diazepan in both generic Lab Farmindustria and VALIUM Lab Roche 10 mg- tablets. Whit this in mind, characterization of the dissolution profiles for both formulation was performed into three medium: HCl 0.1N pH 1.2, Acetate Buffer pH 4.5, and Phosphate buffer pH 6.8, according to the bioequivalency in vitro studies established by OMS. Dissolution profiles were analysed following zero-order, first-order, cube root, Higuchi’s, Weibull’s and similarity factor (f2) models. The first-order kinetic model and Weibull function best characterized of the dissolution profiles of both presentations. The dissolution rate constants of both formulations were similar at pH 1.2, 0.19019 min-1 for VALIUM ® and 0.16641 min-1 for generic Diazepam (p> 0.05), and factor analysis of similarity factor gave values below the range in the three media tested (f2 <50). Hence, we conclude that the dissolution profiles of generic diazepam 10 mg tablets-Lab. Farmindustria and Valium ® 10 mg - Lab ROCHE are not similar